2017
DOI: 10.1038/s41598-017-05047-z
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid affects Lung Adenocarcinoma growth by inducing differentiation via GATA6 activation and EGFR and Wnt inhibition

Abstract: A fundamental task in cancer research aims at the identification of new pharmacological therapies that can affect tumor growth. Differentiation therapy might exploit this function not only for hematological diseases, such as acute promyelocytic leukemia (APML) but also for epithelial tumors, including lung cancer. Here we show that Retinoic Acid (RA) arrests in vitro and in vivo the growth of Tyrosine Kinase Inhibitors (TKI) resistant Non Small Cell Lung Cancer (NSCLC). In particular, we found that RA induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Retinoic acid induces the expression of GATA6 in a variety of contexts 39 , 40 and induces GATA6+ compartment expansion in mouse HF 23 . Isotretinoin ( 13 -cis-retinoic acid) undergoes intracellular isomerisation to all-trans retinoic acid (RA) which then binds to RAR 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Retinoic acid induces the expression of GATA6 in a variety of contexts 39 , 40 and induces GATA6+ compartment expansion in mouse HF 23 . Isotretinoin ( 13 -cis-retinoic acid) undergoes intracellular isomerisation to all-trans retinoic acid (RA) which then binds to RAR 41 .…”
Section: Resultsmentioning
confidence: 99%
“…GATA6 and HOPX also synergistically inhibit the metastatic potential of ADC cells by regulating the transcriptional process of airway epithelial differentiation and malignant invasion . Retinoic acid (RA) promotes upregulation of GATA6 gene expression, which in turn leads to inhibition of epidermal growth factor receptor transcriptional repression and Wnt signaling activation, arresting the in vitro and in vivo growth of tyrosine kinase inhibitors (TKIs) resistant NSCLC …”
Section: Gata6 and Human Cancersmentioning
confidence: 99%
“…26 Retinoic acid (RA) promotes upregulation of GATA6 gene expression, which in turn leads to inhibition of epidermal growth factor receptor transcriptional repression and Wnt signaling activation, arresting the in vitro and in vivo growth of tyrosine kinase inhibitors (TKIs) resistant NSCLC. 27 MicroRNAs (miRNAs) are small non-coding RNAs of~22 nucleotides in length that play important roles in cell growth, development, differentiation, and apoptosis. 28 Studies have shown that miRNAs are clearly differentially expressed in different cancer types, and that the expression of certain miRNAs can serve as both a marker for cancer development and a target for cancer treatment, suggesting that miRNAs may be licensed as oncogenes or tumor suppressors.…”
Section: Gata6 and Lung Cancermentioning
confidence: 99%
“…While the downregulation of MYCN by RAs was reported previously [56,57], we are the first to define the regulation of PLAGL2 and miR-506-3p expressions by RAs. Although RAs have been identified as differentiation agents of cancer cells since 1970s [58][59][60][61][62][63][64][65][66] and have been used to treat neuroblastoma for decades, the molecular mechanisms underlying such function are still poorly understood. RAs are thought to regulate gene transcriptions by binding to RA receptors RAR and RXR, which are TFs that regulate gene expression by binding to the Retinoic Acid Response Elements (RARE) in the target genes [56].…”
Section: Discussionmentioning
confidence: 99%